Role model rules in legislation (Journal of actual problems of jurisprudence, 2019)
The problem of the place and role model laws in the legislative authorities in the countries of the Commonwealth ofIndependent States. The author analyzes the different perspectives on the problem of the ambiguity of the relationshipto the model laws as a means of unification and harmonization of legislation.Key words: model law, model lawmaking, model legislation, the model code.